2017
DOI: 10.1038/s41467-017-01220-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies the SERPINB gene cluster as a susceptibility locus for food allergy

Abstract: Genetic factors and mechanisms underlying food allergy are largely unknown. Due to heterogeneity of symptoms a reliable diagnosis is often difficult to make. Here, we report a genome-wide association study on food allergy diagnosed by oral food challenge in 497 cases and 2387 controls. We identify five loci at genome-wide significance, the clade B serpin (SERPINB) gene cluster at 18q21.3, the cytokine gene cluster at 5q31.1, the filaggrin gene, the C11orf30/LRRC32 locus, and the human leukocyte antigen (HLA) r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
12

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 70 publications
(96 reference statements)
1
62
0
12
Order By: Relevance
“…This model proposes that compromised epithelial barriers promote sensitization to food and airway allergens and to wheezing illnesses in early life 35, 50 . In fact, childhood onset specific loci identified here have been associated with atopic dermatitis or food allergies, such as FLG on 1q21·3 with the atopic march 45 , atopic dermatitis 3133 and food allergies 2830 , KIF3A on 5q31.1 and AP5B1 / OVOL1 on 11q13.1 with the the atopic march 45 and atopic dermatitis 51 , SERPINB7 on 18q21.33 with food allergies 43 , and CRNN (cornulin) on 1q21·3 with atopic dermatitis concomitant with asthma and reduced expression in atopic dermatitis-affected skin 52 . Variants at those loci were all associated with earlier age of asthma onset.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This model proposes that compromised epithelial barriers promote sensitization to food and airway allergens and to wheezing illnesses in early life 35, 50 . In fact, childhood onset specific loci identified here have been associated with atopic dermatitis or food allergies, such as FLG on 1q21·3 with the atopic march 45 , atopic dermatitis 3133 and food allergies 2830 , KIF3A on 5q31.1 and AP5B1 / OVOL1 on 11q13.1 with the the atopic march 45 and atopic dermatitis 51 , SERPINB7 on 18q21.33 with food allergies 43 , and CRNN (cornulin) on 1q21·3 with atopic dermatitis concomitant with asthma and reduced expression in atopic dermatitis-affected skin 52 . Variants at those loci were all associated with earlier age of asthma onset.…”
Section: Discussionmentioning
confidence: 77%
“…S100A12 has been previously implicated in asthma 38 and FLG variants have been associated with atopic dermatitis and food allergies, and asthma in the context of other allergic diseases 21, 2834 . Other childhood onset specific genes previously implicated in asthma but not previously reported in asthma GWASs are CCL20 39 at 2q36.3 and TLR10 40 at 4p14 in whole blood, and TLR6 41, 42 at 4p14, AP5B1 at 11q13.1 and SERPINB7 43 at 18q21·33 in skin.…”
Section: Resultsmentioning
confidence: 87%
“…Previous work has shown that neurogenesis and the earliest phases of neuronal differentiation are compromised by spindle misorientation (51). Furthermore, KIZ is associated with systemic lupus erythematosus (53), and peanut allergy (54). These associations indicate a possible role of KIZ in immune response, a mechanism which is also implicated in TS etiology (55).…”
Section: Discussionmentioning
confidence: 94%
“…We also identified five GWAS with either food or peanut allergy as an outcome. Four of these were carried out in children, and the other was carried out in a population across the ages of 1‐93 years …”
Section: Resultsmentioning
confidence: 99%
“…Included studies were of varying sample sizes with the smallest study having 30 food allergy Caucasian cases and 35 nonallergic Caucasian controls, while the largest study was a GWAS with 2197 European subjects (671 with food allergy, 144 nonallergic nonsensitized controls and 1382 European controls of uncertain phenotype) . The majority (n = 11) of included studies were conducted in only “Caucasian,” “European” or “White” populations, whereas 11 studies were carried out in predominantly Caucasian populations alongside other ethnicities (“Asians,” “Mixed” and “African American”) . Four others were carried out in Japanese populations, one was carried out in a Taiwanese population, and there were five studies where ethnicity was not mentioned …”
Section: Resultsmentioning
confidence: 99%